Expression and significance of INTS10 and IRF3 in chronic hepatitis B patients - Ye, Aizhu; Chen, Xiao; Qiu, Dongbiao; Wu, Wennan (Frontiers in Microbiology, 2025)
IntroductionHepatitis B virus (HBV) infection continues to pose a significant global health challenge, affecting millions of individuals worldwide. Persistent HBV infection is acknowledged as a complex and polygenic process influenced by virological, environmental, and host genetic factors. Previous in vitro studies have indicated that INTS10 inhibits HBV replication in a manner dependent on interferon regulatory factor 3 (IRF3). Nevertheless, the relationships among INTS10 expression, IRF3, and HBV replication in patients with chronic hepatitis B (CHB) have not been comprehensively examined. Thus, this study aimed to investigate the associations between INTS10, IRF3, and HBV replication in CHB patients.MethodsA total of 127 treatment-naïve CHB patients were recruited and categorized into hepatitis B e antigen (HBeAg)-negative and HBeAg-positive groups. Quantitative PCR was utilized to quantify INTS10 and IRF3 expression levels, alongside serum HBV DNA load and conventional liver biochemical parameters, to evaluate HBV infection status.ResultsOur findings revealed significantly lower expression levels of both INTS10 and IRF3 in HBeAg-positive patients compared to their HBeAg-negative counterparts. Additionally, a positive correlation was observed between IRF3 and INTS10 expression. In HBeAg-positive CHB patients, INTS10 and IRF3 levels exhibited negative correlations with HBV DNA, HBeAg, hepatitis B surface antigen (HBsAg), and total bile acid (TBA) levels. Conversely, no significant correlations were detected between INTS10 or IRF3 and these virological and biochemical markers in HBeAg-negative patients.DiscussionThese results suggest that the relationship between INTS10 and IRF3 expression may be modulated by HBeAg status. This implies a potential involvement of HBeAg in the antiviral mechanisms mediated by INTS10 and IRF3 in CHB. Consequently, our study offers valuable insights that may contribute to enhanced clinical management of HBV infection.